Asset mapping score analysis: a novel public health research methodology applied to maternal and child health resources in New Orleans - Jack Healy; Shokufeh Ramirez; Megan Knapp; Carolyn Johnson (BMC, 2023)
Abstract Background Asset mapping is a commonly used method in public health to identify and describe the resources within a community. However, there is currently a lack of standardization in the methods used for asset mapping, which can make it difficult for users to apply the method and compare results between different studies. In this article, we present a new approach called Asset Mapping Score Analysis (AMSA), which is a framework for collecting and organizing data on community assets. We provide an example of the AMSA method through its application in the evaluation of maternal and child health resources in New Orleans, Louisiana. Results The AMSA approach consists of five steps and results in a data collection tool that uses a scoring system to quantify the functional and content areas defined by the users. This method is flexible, reproducible, quantitative, inexpensive, and can be adapted to fit the needs of different geographic areas and fields of study. It can also be repeated over time to monitor changes in systems. We conducted a pilot study to examine the participation of local maternal and child health organizations in four functional areas (education, direct services, policy/advocacy, and research) and 22 content areas. Conclusions In addition to describing the AMSA method and providing an example of its application, we also discuss the methodological issues involved in using the AMSA approach. These include considerations related to study design, data analysis, and interpreting results. We assess the strengths, limitations, and potential future directions of the AMSA method. Finally, we present the results of our AMSA study on maternal and child health organizations in New Orleans to illustrate the utility of this approach. Our findings suggest that the AMSA method is a valuable tool for understanding and characterizing the assets and resources within a community.